Suzaku detection of enigmatic geocoronal solar wind charge exchange event associated with coronal mass ejection. (9th January 2019) - Ishi, Daiki; Ishikawa, Kumi; Numazawa, Masaki; Miyoshi, Yoshizumi; Terada, Naoki; Mitsuda, Kazuhisa; Ohashi, Takaya; Ezoe, Yuichiro
Abstract: Suzaku detected an enhancement of the soft X-ray background associated with solar eruptions on 2013 April 14–15. The solar eruptions were accompanied by an M6.5 solar flare and a coronal mass ejection with magnetic flux ropes. The enhanced soft X-ray background showed a slight variation over half a day and then a clear one in a few hours. The former spectrum was composed of oxygen emission lines, while the later one was characterized by a series of emission lines from highly ionized carbon to silicon. The soft X-ray enhancement originated from geocoronal solar wind charge exchange. However, there appeared to be no significant time correlation with the solar wind proton flux measured by the ACE and WIND satellites. From other solar wind signatures, we considered that an interplanetary shock associated with the coronal mass ejection and a turbulent sheath immediately behind the shock compressed the ambient solar wind ions and then resulted in the soft X-ray enhancement. Furthermore, the enriched emission lines were presumed to be due to an unusual set of ion abundances and ionization states within the coronal mass ejection. We found a better time correlation with the solar wind alpha flux rather than the solar wind proton flux. Our results suggest that the solar wind proton flux is not always a good indicator of geocoronal solar wind charge exchange, especially associated with coronal mass ejections. Instead, the solar wind alpha flux should be investigated when such a soft X-ray enhancement is detected in astronomical observations.